Tenascin promotes cerebellar granule cell migration and neurite outgrowth by different domains in the fibronectin type III repeats (The Rockefeller University Press, 1992)
The extracellular matrix molecule tenascin has been implicated in neuron-glia recognition in the developing central and peripheral nervous system and in regeneration. In this study, its role in Bergmann glial process-mediated neuronal migration was assayed in vitro using tissue explants of the early postnatal mouse cerebellar cortex. Of the five mAbs reacting with nonoverlapping epitopes on tenascin, mAbs J1/tn1, J1/tn4, and J1/tn5, but not mAbs J1/tn2 and J1/tn3 inhibited granule cell migration. Localization of the immunoreactive domains by EM of rotary shadowed tenascin molecules revealed that the mAbs J1/tn4 and J1/tn5, like the previously described J1/tn1 antibody, bound between the third and fifth fibronectin type III homologous repeats and mAb J1/tn3 bound between the third and fifth EGF-like repeats. mAb J1/tn2 had previously been found to react between fibronectin type III homologous repeats 10 and 11 of the mouse molecule (Lochter, A., L. Vaughan, A. Kaplony, A. Prochiantz, M. Schachner, and A. Faissner. 1991. J. Cell Biol. 113:1159-1171). When postnatal granule cell neurons were cultured on tenascin adsorbed to polyornithine, both the percentage of neurite-bearing cells and the length of outgrowing neurites were increased when compared to neurons growing on polyornithine alone. This neurite outgrowth promoting effect of tenascin was abolished only by mAb J1/tn2 or tenascin added to the culture medium in soluble form. The other antibodies did not modify the stimulatory or inhibitory effects of the molecule. These observations indicate that tenascin influences neurite outgrowth and migration of cerebellar granule cells by different domains in the fibronectin type III homologous repeats.